Development of Gamification-based Microlearning Media for Learning Integers - Shaumi Rani; Yerry Soepriyanto; Agus Wedi; Made Duananda Kartika Degeng (JTP - Jurnal Teknologi Pendidikan, 2025)
Learning integers at the junior high school level often faces obstacles in the form of low student understanding and engagement, mainly due to the abstract nature of the material and the learning approaches that are still dominated by conventional methods. Therefore, it is necessary to develop learning media that can present material concisely, interestingly, and relevant to the characteristics of students. This study aims to develop gamification-based microlearning media on a Learning Management System (LMS) platform specifically designed for integer material at the junior high school level, and to examine its feasibility for classroom use. The novelty of this study lies in the integration of microlearning and gamification in a media development design for the context of integer learning, which is still rarely studied in previous studies. This study uses the Research and Development method with the Web-Based Instructional Design (WBID) model as the development framework. The research subjects consisted of 32 students at a junior high school selected using a purposive sampling technique. Data were collected through expert validation, student response questionnaires, LMS analytics, and were analyzed using descriptive quantitative and qualitative techniques. The results of the validation by material and media experts obtained an average score of 87.5% and 90%, respectively, with the category of very valid. The limited trial and full implementation showed excellent results with percentages of 86.05% and 87%, respectively. Summative evaluations showed that 27 of 32 students completed the learning on time, 30 of 32 students earned engagement badges, and the majority accessed the LMS consistently every week. These findings provide empirical evidence that the developed gamification-based microlearning media is effective in increasing engagement and supporting integer learning. However, this study is limited by the sample size and has not yet measured the direct impact on academic learning outcomes.